Removal of duplicate image on What’s App media - Atkar, Harshada; Satikosare, Komal; Panjwani, Sanjana (International Journal of Computer Sciences and Engineering, 2025)
An extreme transaction of what is the application that is multiple files duplicated or replicated. Where complete documents can be offered in different formats such as JPG, JPEG, PNG. These files can be copied to avoid delays / consumption of data to provide failover. The large databases of what application files stored in the effort to declassify with receiving folders. Copies of files are abundant in images in databases. In our discussion on the social network imaging line (What’s App), over 60% of the total data are exact duplicates. Due to re-sending by friends with connected together. In this algorithm to detect replicated files before storing them in the local database, check with a given hash index, which is more important in applications where What’s App data sources or groups of links received from many friends. Duplicating file deduction is very necessary to reduce consumption data at runtime, to improve data storage capacity with greater accuracy.